Child Development Measurement Instrument Based on Digital Format at the Childcare Center - Rinekasari, Nenden Rani; Achdiani, Yani; Arlianty, Lia Shafira; Jubaedah, Yoyoh; Rohaeni, Neni; Inten, Dinar Nur (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2024)
The rapid development of technology affects the development of instruments for measuring child development. The tool developed follows Permendikbud RI No. 137 of 2014 by utilizing technology based on the digital format of Jotform. This study aimed to create a digital format-based child social-emotional development measurement instrument at the Ceria Anak Foster Care Park (TARA). This research uses a mixed method with an (RD) approach and uses the ADDIE research model (analysis, design, development, implementation, and evaluation). Data collection techniques were conducted through interviews and validation tests through the expert judgment of measurement, material, and I.T. experts. Then a limited trial implementation was carried out on 2-3-year-old children in a foster park for children. The results of expert judgment show that the measurement instrument for social-emotional development using the Jotform application in the TARA program is declared very feasible with revisions. The percentage of the feasibility of the measurement instrument is 100%, the rate of material feasibility is 88%, and the portion of application feasibility is 100%. The results of the limited trial implementation show that the measurement instrument of children's social-emotional development using the Jotform application in the home-based childcare program is feasible to use. The percentage of the feasibility of the measurement instrument after being implemented with a limited trial was 72.6%. Recommendations for further research can test the effectiveness of measuring children's socio-emotional development using the Jotform digital format to implement child assistance at the daycare or childcare.